311CARDIAC SURGERY UNDER COUMADIN: IS PREOPERATIVE NORMALISATION OF THE INTERNATIONAL NORMALISED RATIO NECESSARY?. (October 2014) - Essa, Y.; Hoyer, H.; Färber, G.; Diab, M.; Hofmann, M.; Amorim, P.; Doenst, T.
Abstract : Objectives: Patients on oral anticoagulation presenting for cardiac surgery are often converted to heparin. We assessed the outcome in patients with preoperative Coumadin undergoing cardiac surgery with international normalised ratio (INR) above or below 1.4. Methods: From November 2007 to September 2013, 117 Coumadin patients presented for cardiac surgery. We divided them into group A ( n = 74, INR > 1.4 at day of surgery) and group B ( n = 43, INR ≤ 1.4 at day of surgery). Results: Patients received a mix of cardiac surgical procedures [coronary bypass graft (CABG), n = 19; valves, n = 56; combinations, n = 27; ventricular assist device (VAD), n = 3; transplantation, n = 12] without group differences. Surgery was elective, urgent or emergent in 63%, 16% or 21%, respectively, again similar in both groups. Preoperative hospital stay was longer in group B (8.3 ± 12.8 days vs 2.3 ± 2.9 days, P =< 0.001). Hospital mortality was high with 27% in group A and 12% in group B ( P = 0.05). Median chest tube drainage (first 24 h) was similar in both groups (median, min, max in group A: 781, 170, 4750 ml; in group B: 800, 300, 3520 ml, respectively). The fraction of patients requiring any transfusion was not significantly higher in group A (64.9% vs 55.8%, P = 0.3). If transfusion was required, group A received more packed red blood cells (median units: 2 vs 1, P = 0.1). The re-exploration rate was 12% in both groups. Multivariate analysis failed to identify preoperative INR as an independent predictor of postoperative bleeding. However, low levels of preoperative fibrinogen predicted increased chest tube drainage ( P = 0.01). Conclusion: Patients presenting for cardiac surgery with preoperative Coumadin represent a high risk population. Bleeding complications or transfusion requirements for these patients do not seem to be influenced by preoperative INR. These results support the need for a randomised trial.